Minimally invasive drug delivery to the cochlea through application of nanoparticles to the round window membrane. (September 2012) - Buckiová, Daniela; Ranjan, Sanjeev; Newman, Tracey A; Johnston, Alexander H; Sood, Rohit; Kinnunen, Paavo KJ; Popelář, Jiří; Chumak, Tetyana; Syka, Josef
Direct drug delivery to the cochlea is associated with the risk of irreversible damage to the ear. In this study, liposome and polymersome nanoparticles (NPs), both formed from amphiphilic molecules (lipids in liposomes and block copolymers in polymersomes), were tested as potential tools for drug delivery to the cochlea via application onto the round window membrane in adult mice (strain C3H). One day after round window membrane application, both types of NPs labeled with fluorescent markers were identified in the spiral ganglion in all cochlear turns without producing any distinct morphological or functional damage to the inner ear. NPs were detected, although to a lesser extent, in the organ of Corti and the lateral wall. The potential of liposome and polymersome NPs as therapeutic delivery systems into the cochlea via the round window membrane was evaluated using disulfiram, a neurotoxic agent, as a model payload. Disulfiram-loaded NP delivery resulted in a significant decrease in the number of spiral ganglion cells starting 2 days postapplication, with associated pronounced hearing loss reaching 20–35 dB 2 weeks postapplication as assessed through auditory brainstem responses. No changes in hair cell morphology and function (as assessed by recording otoacoustic emissions) were detected after disulfiram-loaded NP application. No effects were observed in controls where solution of free disulfiram was similarly administered. The results demonstrate that liposome and polymersome NPs are capable of carrying a payload into the inner ear that elicits a biological effect, with consequences measurable by a functional readout. Original submitted 15 March 2011; Revised submitted 4 January 2012; Published online 4 April 2012